A Task-Shifting Problem-Solving Therapy Intervention for Depression and Barriers to Antiretroviral Therapy Adherence for People Living With HIV in Zimbabwe: Case Series. Issue 1 (February 2020) - Nyamayaro, Primrose; Bere, Tarisai; Magidson, Jessica F.; Simms, Victoria; O'Cleirigh, Conall; Chibanda, Dixon; Abas, Melanie
Abstract: HIV is prevalent in Sub-Saharan Africa, and depression frequently co-occurs. Depression is one of the most important predictors of poor adherence to antiretroviral therapy (ART). Little has been done to develop integrated interventions that are feasible and appropriate for task-shifting to nonspecialists that seek to address both depression and barriers to ART adherence in Sub-Saharan Africa. This case series describes an integrated intervention for depression and ART adherence delivered by a lay adherence counselor and supervised by a local psychologist. The 6-session intervention was based on problem-solving therapy for depression and for barriers to adherence (PST-AD), with stepped care for those whose depression did not recover with PST-AD. Primary outcomes were acceptability and depression. Acceptability was measured by participant attendance to the 6 sessions. Three case studies illustrate the structured intervention, solutions identified to adherence barriers and to problems underlying low mood, and changes seen in the participant's psychological symptoms. Acceptability of the intervention was high and common mental disorder symptoms scores measured using the SRQ-8 decreased overall. An integrated intervention for depression and adherence to ART appeared feasible in this low-income setting. An RCT of the intervention versus an appropriate comparison condition is needed to evaluate clinical and cost-effectiveness. Highlights: An integrated intervention for depression and ART adherence delivered by a lay adherence counsellor in a low income country Acceptability of the intervention as measured by patient's attendance was high The integrated intervention was feasible as indicated by the counsellor's ability to deliver the intervention The intervention was associated with a reduction in depression symptoms